MAGNETIC STUDY OF SIDOARJO HOT MUD (LUSI) AND ITS CONTRIBUTION IN THE PREDICTION OF MUD'S ORIGIN - RIFAI (NIM 30203004), HAMDI
A study of magnetic properties of mud erupted in district Porong, Sidoarjo, East Java termed LUSI has been carried out to comprehensively identify its magnetic minerals. These information on magnetic mineralogy as well magnetic grain size and grain shape are expected to reveal the source of LUSI. To prevent sample contamination that could affect its magnetic and physical properties, LUSI sample was taken only 20 m from the main crater. Sample acquisition was carried out in two phases. Phase one was held on January 22 2007 while the second phase was between February 20 and March 29 of 2007. The physical and magnetic properties of phase one samples were used as baseline for that of phase two. Certain physical parameters, such as temperature was measured using a mercury-based thermometer directly on site inside a clamp-shell bucket. Other physical parameters, such as dry mass, wet mass, density, and sedimentation rate were measured in the laboratory. Certain magnetic parameters of the bulk samples, such as magnetic susceptibility (?), anhysteretic remanent magnetization (ARM) and isothermal remanent magnetization (IRM) were also measured along with measurements of temperature dependent susceptibility (TDS) and hysteresis parameters on extracted magnetic grains. Analysis on the magnetic properties was also complemented by XRD (X-Ray diffraction) and EDX-equipped SEM (scanning electron microscopy).